KAWA TRADITIONAL VILLAGE AS A CULTURAL TOURISM DESTINATION: CULTURAL HERITAGE POTENTIAL, LANDSCAPE BEAUTY, AND ACCESSIBILITY CHALLENGES - katarina dhiki; Maria Yosefa Bupu Ogi; Sisilia Helena Jolin Tadu Lado Tadu Lado (SOSIOEDUKASI, 2026)
ABSTRACT This study aims to identify and analyze the potential of Kawa Traditional Village in Nagekeo Regency as a cultural tourism destination, focusing on cultural heritage, landscape beauty, and accessibility challenges. A qualitative descriptive approach was employed to examine the actual conditions of the village through observation, semi-structured interviews, and documentation. Data were primarily obtained from the customary leader of Kawa Village as the key informant and supported by informal information from community members. The findings indicate that Kawa Traditional Village possesses significant cultural heritage potential, reflected in 13 traditional houses, the Kawa clan-based kinship system, local wisdom, and customary rituals. These cultural elements remain actively practiced and contribute to the authenticity of the destination. The village also has considerable landscape beauty, characterized by traditional settlements, agricultural areas, savanna, hills, and mountain scenery between Mount Amagelu and Mount Ebulobo, forming an integrated cultural landscape shaped by interactions between the community and its natural environment. However, accessibility remains a major challenge. The existing concrete road has deteriorated due to water erosion, limiting access for automatic scooters and four-wheeled vehicles, while adequate directional signs and information boards are also lacking. Therefore, the development of Kawa Traditional Village as a cultural tourism destination requires sustainable improvements in accessibility while preserving cultural authenticity, environmental quality, and community involvement.